Concerted activity of IgG1 antibodies and IL-4/IL-25-dependent effector cells trap helminth larvae in the tissues following vaccination with defined secreted antigens, providing sterile immunity to challenge infection - Hewitson, James P.; Filbey, Kara J.; Bieren, Julia Esser-Von; Camberis, Mali; Schwartz, Christian; Murray, Janice; Reynolds, Lisa A.; Blair, Natalie; Robertson, Elaine; Harcus, Yvonne; Boon, Louis; Huang, Stanley Ching-Cheng; et al. (PLoS Pathogens, 2015)
Over 25% of the world's population are infected with helminth parasites, the majority of which colonise the gastrointestinal tract. However, no vaccine is yet available for human use, and mechanisms of protective immunity remain unclear. In the mouse model of Heligmosomoides polygyrus infection, vaccination with excretory-secretory (HES) antigens from adult parasites elicits sterilising immunity. Notably, three purified HES antigens (VAL-1, -2 and -3) are sufficient for effective vaccination. Protection is fully dependent upon specific IgG1 antibodies, but passive transfer confers only partial immunity to infection, indicating that cellular components are also required. Moreover, immune mice show greater cellular infiltration associated with trapping of larvae in the gut wall prior to their maturation. Intra-vital imaging of infected intestinal tissue revealed a four-fold increase in extravasation by LysM+GFP+ myeloid cells in vaccinated mice, and the massing of these cells around immature larvae. Mice deficient in FcR? chain or C3 complement component remain fully immune, suggesting that in the presence of antibodies that directly neutralise parasite molecules, the myeloid compartment may attack larvae more quickly and effectively. Immunity to challenge infection was compromised in IL-4R?- and IL-25-deficient mice, despite levels of specific antibody comparable to immune wild-type controls, while deficiencies in basophils, eosinophils or mast cells or CCR2-dependent inflammatory monocytes did not diminish immunity. Finally, we identify a suite of previously uncharacterised heat-labile vaccine antigens with homologs in human and veterinary parasites that together promote full immunity. Taken together, these data indicate that vaccine-induced immunity to intestinal helminths involves IgG1 antibodies directed against secreted proteins acting in concert with IL-25-dependent Type 2 myeloid effector populations.
EVALuna2:25873